The Relationship between Family Communication and Smoking Behavior in The Teenagers in Rawa Semut RT 09 Margahayu East Bekasi in 2022 - Sinaga, Ribka Sulastri; Agustina, Lisna; Hidayati Bunga, Dinda Nur Fajri (Rena Cipta Mandiri, 2025)
Teenager is a critical period when a person moves from childhood to a period where at this time teenagers will be faced with the usual deviations at that time such as smoking behavior. According to WHO data in 2020, around 225,700 people in Indonesia died from smoking or other related diseases. Factors that can influence smoking behavior is family factors, one of which is family communication. This study was conducted to determine the relationship between family communication and smoking behavior in teenagers in Rawa Semut RT 09 Margahayu East Bekasi in 2022. The research method is a quantitative type with an analytic approach with a cross-sectional approach. The population of this study was teenagers in Rawa Semut RT 09 Margahayu East Bekasi with a sample of 49 respondents using the Non-Probability Sampling technique with the type of Purposive Sampling. The instrument of this research used the family communication and behavior smoking questionnaire. Based on the results of the value analysis using the chi-square test, a p-value of 0,000 ≤ 0,05 was obtained. There is a significant relationship between family communication and smoking behavior in teenagers in Rawa Semut RT 09 Margahayu East Bekasi in 2022.